2005
DOI: 10.1124/jpet.105.091801
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Hyperpolarization-Activated, Cyclic Nucleotide-Gated Channel Function by the Intravenous General Anesthetic Propofol

Abstract: Propofol (2,6-diisopropylphenol) is a widely used intravenous general anesthetic, which has been reported to produce bradycardia in patients at concentrations associated with profound sedation and loss of consciousness. Hyperpolarizationactivated, cyclic nucleotide-gated (HCN) channels conduct a monovalent cationic current I h (also known as I q or I f ) that contributes to autorhythmicity in both the brain and heart. Here we studied the effects of propofol on recombinant HCN1, HCN2, and HCN4 channels and foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 41 publications
6
48
0
1
Order By: Relevance
“…Native neuronal I h as well as heterologously expressed HCN channels are inhibited by clinically relevant concentrations (Յ0.5 mM) of the inhalational anesthetics halothane and isoflurane (59,87). Similarly, the intravenous anesthetic propofol inhibits and slows the activation of native and expressed HCN channels (67,233).…”
Section: B Blockers Of Neuronal I Hmentioning
confidence: 99%
“…Native neuronal I h as well as heterologously expressed HCN channels are inhibited by clinically relevant concentrations (Յ0.5 mM) of the inhalational anesthetics halothane and isoflurane (59,87). Similarly, the intravenous anesthetic propofol inhibits and slows the activation of native and expressed HCN channels (67,233).…”
Section: B Blockers Of Neuronal I Hmentioning
confidence: 99%
“…Several molecules are known to interact with funny channels. Early studies showed for example that external Cs ϩ and Rb ϩ ions reduce I f 94 ; these ions, however, along with other molecules also reducing I f , such as THA (9-amino-1,2,3,4-tetrahydroacridine, 95 clonidine, 96 and propofol, 97 interact with other channels and mechanisms and are far from specific. Substances able to slow heart rate by selective f-channel block were developed in the 80's and termed "pure bradycardic agents" (PBAs).…”
Section: Pharmacological Evidencementioning
confidence: 99%
“…The intravenous general anesthetic propofol (2,6-diisopropylphenol) preferentially inhibits HCN1 with respect to HCN2, 3, and 4 (Cacheaux et al, 2005;Chen et al, 2005) and has a modest pharmacokinetic preference for the periphery, that is, plasma levels associated with anesthesia are higher than those in cerebrospinal fluid (CSF) ( Table 1). However, its hypnotic properties and its potentiation of type A GABA receptor (GABA A -R) activity (Franks, 2008) limit its routine use as an analgesic, even at low concentrations.…”
Section: Introductionmentioning
confidence: 99%